Further Results about Traveling Wave Exact Solutions of the (2+1)-Dimensional Modified KdV Equation - Yang Yang; Jian-ming Qi; Xue-hua Tang; Yong-yi Gu (Advances in Mathematical Physics)
We used the complex method and the exp(-ϕ(z))-expansion method to find exact solutions of the (2+1)-dimensional mKdV equation. Through the maple software, we acquire some exact solutions. We have faith in that this method exhibited in this paper can be used to solve some nonlinear evolution equations in mathematical physics. Finally, we show some simulated pictures plotted by the maple software to illustrate our results.